2020
DOI: 10.1002/nag.3176
|View full text |Cite
|
Sign up to set email alerts
|

One‐dimensional consolidation of layered soils under ramp load based on continuous drainage boundary

Abstract: The traditional drainage boundary regards the drainage boundary as completely permeable or completely impervious. However, the drainage boundary is an impeded drainage boundary between completely permeable and impervious in engineering practice. In view of this, a new drainage boundary, namely the continuous drainage boundary, is introduced in this paper to study the consolidation problem of layered soils. First, the governing equations for the one-dimensional consolidation problem of layered soils subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…This theory as well as its variations has dominated the literature in the past several decades. In the context of one-dimensional deformation and flow processes, some major improvements on the theory have been made taking into consideration the effect of partial saturation, [1][2][3][4][5][6][7][8][9][10] time-dependent surface loading, [11][12][13][14][15][16][17] layered soil systems, [18][19][20][21][22][23][24] and simple nonlinearity including plasticity [25][26][27][28] and varying compressibility and permeabilitiy, 23,[29][30][31][32][33] among others. Even though the 1D kinematics have imposed limits on the applicability of these theories, they are still valuable contributions to the literature because they can be represented with closed-form analytical solutions.…”
Section: Introductionmentioning
confidence: 99%
“…This theory as well as its variations has dominated the literature in the past several decades. In the context of one-dimensional deformation and flow processes, some major improvements on the theory have been made taking into consideration the effect of partial saturation, [1][2][3][4][5][6][7][8][9][10] time-dependent surface loading, [11][12][13][14][15][16][17] layered soil systems, [18][19][20][21][22][23][24] and simple nonlinearity including plasticity [25][26][27][28] and varying compressibility and permeabilitiy, 23,[29][30][31][32][33] among others. Even though the 1D kinematics have imposed limits on the applicability of these theories, they are still valuable contributions to the literature because they can be represented with closed-form analytical solutions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the permeability coefficients and compression moduli of subsoils and gravel columns are constant during the drainage process in the proposed methods. The proposed analytical solutions will be promoted if the time‐dependent variations of these consolidation‐related parameters are involved 28,29 . In addition, the proposed analytical solutions are expected to spread into more circumstances, such as unsaturated soft soils causing varying negative and positive friction along the pile shaft 30,22 and nonlinear constitutive models of subsoils 31,32 …”
Section: Discussionmentioning
confidence: 99%
“…To explore the consolidation characteristics of clay considering the effects of temperature, many related experimental studies were carried out 19,29–37 . Paaswell carried out the heating test of soils under constant loading and found that the increase in temperature d led to the soil settlement, where the concept of “thermal consolidation” was proposed for the first time 29 .…”
Section: Introductionmentioning
confidence: 99%
“…To explore the consolidation characteristics of clay considering the effects of temperature, many related experimental studies were carried out. 19,[29][30][31][32][33][34][35][36][37] Paaswell carried out the heating test of soils under constant loading and found that the increase in temperature d led to the soil settlement, where the concept of "thermal consolidation" was proposed for the first time. 29 Some experimental researches showed that the influence of temperature on the compressibility of clay was related to the stress history, 33,34 and the pre-consolidation pressure of soils gradually decreased with increasing the temperature.…”
mentioning
confidence: 99%